Magnetic Resonance Imaging Investigation of Neuroplasticity After Ischemic Stroke in Tetramethylpyrazine-Treated Rats - Feng, Xue-Feng; Lei, Jian-Feng; Li, Man-Zhong; Zhan, Yu; Yang, Le; Lu, Yun; Li, Ming-Cong; Zhuang, Yu-Ming; Wang, Lei; Zhao, Hui (Frontiers in Pharmacology, 2022)
Ischemic stroke elicits white matter injury typically signed by axonal disintegration and demyelination, thus the development of white matter reorganization is needed. 2,3,5,6-Tetramethylpyrazine (TMP) is widely used to treat ischemic stroke. This study was aimed to investigate whether TMP could protect white matter and promote axonal repair after cerebral ischemia. Male Sprague-Dawley rats were subjected to permanent middle cerebral artery occlusion (MCAO) and treated with TMP (10, 20, 40 mg/kg) intraperitoneally for 14 days. The motor function related to gait was evaluated by gait analysis system. Multi-parametric magnetic resonance imaging (MRI) was conducted to noninvasively identify gray-white matter structural integrity, axonal reorganization and cerebral blood flow (CBF) followed by histological analysis. The expressions of axonal growth associated protein-43 (GAP-43), synaptophysin (SYN), axonal growth-inhibitory signals and guidance factors were measured with western blot. Our results showed TMP reduced infarct volume, relieved gray-white matter damage, promoted axonal remodeling and restored CBF along the peri-infarct cortex, external capsule and internal capsule. These MRI findings were confirmed by histopathological data. And motor function especially gait impairment was improved by TMP treatment. Notably, TMP upregulated GAP-43, SYN, enhanced axonal guidance cues Netrin-1/DCC and Slit-2/Robo-1, while downregulated intrinsic growth-inhibitory signals NogoA/NgR and RhoA/ROCK-2. Taken together, our data indicated that TMP facilitated poststroke axonal remodeling and motor functional recovery. Moreover, our findings suggested that TMP restored local CBF, augmented guidance cues and restrained intrinsic growth-inhibitory signals. All of which might improve the intracerebral microenvironment of ischemic areas and then benefit white matter remodeling.